INFORMATION TECHNOLOGY-BASED COLLABORATIVE GOVERNANCE INNOVATION IN PUBLIC SERVICES - Rif'ah Hisbiyah Aimmatul Khoir; Aminullah (International Journal of Multidisciplinary Reseach, 2026)
This research endeavors to investigate and dissect innovations in information technology-enabled collaborative governance as a means to augment the caliber of public services within Indonesia. In an era characterized by digital advancements, the provision of public services that are both effective and efficient remains a paramount societal expectation, thereby underscoring the need for a collaborative governance framework bolstered by the judicious application of information technology. This inquiry adopts a systematic literature review (SLR) approach, consulting scholarly publications, policy assessments, and official governmental records. The findings suggest that the incorporation of information technology into the collaborative governance paradigm leads to a substantial improvement in citizen engagement, transparency, accountability, and the operational effectiveness of governmental services. Key advancements identified encompass unified e-government frameworks, inter-agency cooperative data systems, and digital citizen feedback mechanisms. The research further highlights significant obstacles to adoption, specifically the disparity in digital access, administrative inertia, and inadequate technological infrastructure in geographically isolated regions. These conclusions are anticipated to offer substantial contributions to the formulation of public service strategies in Indonesia that are more equitable, adaptable, and forward-thinking, while simultaneously outlining a course toward practical remedies with tangible societal benefits.